Avaliação institucional, as relações de saber e poder na universidade: regulação e auto-avaliação - Santana, Margarida Conceição Cunha (2007)
This thesis discusses Brazilian university, the relationship between knowledge and power and their effects on the social function that constructs knowledge and citizenship, as well as institutional autonomy and otherness. The discussion focuses, first, the institutional evaluation as an evaluator instrument of the State that controls and regulates university and, in the other hand, like a process capable to promote self-knowledge by the way of self-evaluation, research and critical reflection in all the levels of academic work. This work is based on Bourdieu s (2005) analyses on the conceits of habitus and field that are applicable to university in the sense of social inequality; on Foucault s (1996, 2001a, 2001b, 2004) discussions on the relationships of tutor and individualizer knowledge and power of State on the formation of subjects by structural relationships that are lived by it; on Chauí s (2001) proposals on resignification of academic autonomy; on Dias Sobrinho s (2000, 2005) studies on evaluation of superior education; and on Habermas (1999) thoughts on rational communication and criticism of self-evaluation. In this work, self-evaluation is understood as an administrative and pedagogical project that could, by the mean of a dialogical practice that is reflexive and critical, answer the questions and the necessities of qualification of academic work and fortify democratic relationships, principals and values of citizenship inside the group of actuation and action of university as an institution of superior thought.